2006
DOI: 10.1158/1535-7163.mct-06-0104
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib (PS-341, Velcade) increases the efficacy of trastuzumab (Herceptin) in HER-2–positive breast cancer cells in a synergistic manner

Abstract: Background: Preclinical and clinical studies have shown that the proteasome inhibitor bortezomib (PS341, Velcade) is highly effective when combined with chemotherapeutic agents. The value of trastuzumab (Herceptin) in HER-2 -positive (3+ score by immunohistochemistry or fluorescence in situ hybridization positive) breast cancer is also known; however, the response rate is <40% for metastatic breast cancer. These two pharmacologic agents prevent nuclear factor-KB (NF-KB) activation and induce nuclear accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…18 In other reports, several sequential combination procedures had been used. Examples include addition of the first drug for 24 h followed by the second drug for a further 48 h, 26 treatment of the first drug for 24 h followed by its removal and addition of the second drug for a further 48 h, 27 targeted therapy for 72 h followed by chemo treatment for 24 h or chemo treatment for 24 h followed by targeted therapy for 48 h, 28 and the first drug for 24 h followed by a second single or add-on drug for 24 h. 29,30 Different means of administration of the drugs may affect the anti-proliferative outcome. Here we used PAC-1 treatment for 48 h and Cis treatment for 24 h (72 h total).…”
Section: Discussionmentioning
confidence: 99%
“…18 In other reports, several sequential combination procedures had been used. Examples include addition of the first drug for 24 h followed by the second drug for a further 48 h, 26 treatment of the first drug for 24 h followed by its removal and addition of the second drug for a further 48 h, 27 targeted therapy for 72 h followed by chemo treatment for 24 h or chemo treatment for 24 h followed by targeted therapy for 48 h, 28 and the first drug for 24 h followed by a second single or add-on drug for 24 h. 29,30 Different means of administration of the drugs may affect the anti-proliferative outcome. Here we used PAC-1 treatment for 48 h and Cis treatment for 24 h (72 h total).…”
Section: Discussionmentioning
confidence: 99%
“…Second, according to recent study and the disappointing results of clinical trials using bortezomib as monotherapy in some solid tumours, it appears that this molecule should be used in combination. In 2006, Cardoso et al (2006) showed a synergy between bortezomib and trastuzumab in HER2/neu þ þ þ / þ þ cell lines. These results convinced the authors to conduct a phase 1 clinical trial that aimed at evaluating this drug combination.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In the meantime, combination of bortezomib with various agents, such as dexamethasone, DNA-damaging drugs, trastuzumab (herceptin) and tipifarnib, have been widely investigated. 13,14 It seems that bortezomib offers great promise to overcome resistance to conventional chemotherapy. 15 More recently, bortezomib was shown to interact synergistically with cyclin-dependent kinase inhibitor flavopiridol and histone deacetylase inhibitor suberoylanilide hydroxamic acid or sodium butyrate to induce apoptosis in Bcr-Abl þ cells.…”
Section: Introductionmentioning
confidence: 99%